Bedhaya Ketawang: A Yogic Perspective on Human Function and Expression as a Means to Comply with the Physical Distancing - Tresya Yuliana Fitri (Javanologi: International Journal of Javanese Studies, 2023)
The study finds that the Movement Patterns performed in Bedhaya Ketawang are fundamental and universal. Hence, the monotony of the dance in indicating the universality of human function and expression for higher mental performance and concentration is justified through the Yogic Approach. This finding implies further studies on specifying ancient cultural and civilisational influence in Javanese Culture at large across eras. The study explains Bhedaya's phenomenon which indicates that the practice could be designed as a social and virtual space for educational purposes. This implies further extensive studies on exploring, structuring and organising the practical application of the recommendations and findings.